High dose-rate endoluminal brachytherapy for primary and recurrent esophageal cancer - Nicolay, Nils; Rademacher, Johanna; Oelmann-Avendano, Jan Tobias; Debus, Jürgen; Huber, Peter E.; Lindel, Katja (Strahlentherapie und Onkologie, 2016)
PurposeThe aim of this work was to evaluate outcomes and toxicities of high dose-rate (HDR) endoluminal brachytherapy in a cohort of esophageal cancer patients.Patients and methodsWe analyzed the records of 36 patients treated with HDR brachytherapy for histologically confirmed esophageal cancer. Brachytherapy was either applied as a boost treatment for definitive treatment regimens or as salvage therapy for recurrent tumors with single doses between 4 and 6 Gy. Survival and toxicities were retrospectively analyzed.ResultsBrachytherapy was performed as initially planned in all but one patient; 18 patients had a complete endoscopic response at the first follow-up examination. Locoregional recurrence was observed in 24 patients after a median time of 3 months; 1‑ and 2‑year recurrence-free survival rates were 51 and 51 % for the patients treated for primary tumors and 11 and 6 % for patients treated for tumor recurrence, respectively. Median overall survival was 18 months; estimated overall survival rates at 1, 2, and 3 years were 63, 50, and 30 % after primary brachytherapy, and 60, 25, and 6 % after recurrence therapy. Adenocarcinoma histology, non-complete remission after treatment, and treatment for recurrent cancers were associated with significantly reduced prognoses. Mild dysphagia was the most common side effect in 17 patients; 8 patients suffered from locoregional grade 3 toxicities, and no grade 4 or 5 toxicities were observed.ConclusionsEndoluminal brachytherapy during the course of esophageal cancer treatment can be safely applied and results in good functional outcomes regarding dysphagia with low rates of severe toxicities.